Western Colonization and the Powerlessness of the Islamic World - Jamilah, Cucu; Trimasary, Ima; Adawiyah, Siti Lutfi Robi’atul; Tabroni, Imam; Jie, Lie; Jixiong, Cai (International Journal of Educational Narratives, 2023)
Background. The Muslim world experienced several second peaks of glory during the reign of three great empires, the Ottoman, Safavid and Mughal (Indian) empires. Purpose. The purpose of this research is to reveal in depth the history of Islam during the 1800-1900 AD and broaden the horizons of knowledge for writers and readers.  Therefore, it is necessary to reveal what factors caused the decline of Islam at that time as well as how the West dominated science at that time? Method. This research uses manuscript studies or known as research with the literature study method.  The study of Islamic history texts in the modern period is also the object of this research which shows how this period displays the decline of Islam and the glory of the West. Results. The three great Islamic empires of the Ottomans, Safavids and Mughals, which were able to "alleviate" the image of Islam from backwardness and subsequently "restore" its reputation in international eyes, lasted only until the seventeenth century. In the following period, it fell back into an atmosphere of decline in many aspects, such as in the political and military fields, economics, and science. Conclusion. In addition, these three Islamic kingdoms did not have the same spirit in the development of science as happened during the first advancement period. Meanwhile, Europe experienced significant progress in various aspects, especially in science, due to the influence of thoughts from figures such as Ibn Rushd and European thinkers who created technological advances such as the steam engine.